Impact on neonatal morbidity of moderate to severe early foetal growth restriction defined by doppler criteria: multicentre study - Jesús Alberto Fuentes Carballal; Marcelino Pumarada Prieto; Pilar Adelaida Crespo Suárez; José Luaces González; Isabel López Conde; Rosaura Picans Leis; Alicia Sardina Ríos; Cristina Durán Fernández-Feijoo; Alejandro Avila-Alvarez (Elsevier, 2024)
Introduction: In recent years, there has been a change in the conceptualization of foetal growth restriction (FGR), which has gone from being defined solely based on weight criteria to being defined and staged based on Doppler criteria. The aim of our study was to evaluate neonatal risk in a cohort of neonates with moderate to severe early-onset FGR defined by Doppler criteria. Population and methods: We conducted a multicentre prospective cohort study in a cohort of neonates with early-onset foetal growth restriction and abnormal Doppler findings and a control cohort without Doppler abnormalities matched for sex and gestational age. Results: A total of 105 patients (50 cases, 55 controls) were included. We found a higher frequency of respiratory morbidity in the FGR group, with an increased need of surfactant (30% vs. 27.3%; OR, 5.3 [95% CI, 1.1−26.7]), an increased need for supplemental oxygen (66% vs. 49.1%; OR, 5.6 [95% CI, 1.5−20.5]), and a decreased survival without bronchopulmonary dysplasia (70 vs. 87.3%; OR, 0.16 [95% CI, 0.03−0.99]). Patients with FGR required a longer length of stay and more days of parenteral nutrition and had a higher incidence of haematological abnormalities such as neutropenia and thrombopenia. The lactate level at birth was higher in the severe FGR subgroup (6.12 vs. 2.4 mg/dL; P = .02). Conclusion: The diagnosis of early-onset moderate to severe FGR defined by Doppler criteria carries a greater risk of respiratory, nutritional and haematological morbidity, independently of weight and gestational age. These patients, therefore, should be considered at increased risk compared to constitutionally small for gestational age preterm infants or preterm infants without FGR. Resumen: Introducción: En los últimos años se ha producido un cambio en el concepto del crecimiento intrauterino retardado (CIR), pasando de estar definido únicamente por criterios de peso a estar definido y estadiado por criterios doppler. Este estudio pretende evaluar el riesgo neonatal de una cohorte de neonatos con CIR precoz moderado-grave definidos por criterios doppler. Población y métodos: Se realizó un estudio multicéntrico de cohortes prospectivo en el que se incluyó una cohorte de neonatos con restricción de crecimiento intrauterino precoz con doppler alterado y una cohorte de control sin alteraciones doppler, pareada por sexo y edad gestacional. Resultados: Se incluyeron un total de 105 pacientes (50 casos, 55 controles). Se encontró mayor morbilidad respiratoria en el grupo CIR, con mayor necesidad de surfactante (30% versus 27,3%, OR IC95% 5,3 [1,1-26,7]), mayor necesidad de oxígeno suplementario (66% versus 49,1% OR IC95% 5,6 [1,5-20.5]), y menor supervivencia sin displasia broncopulmonar (70 vs. 87,3% OR IC95% 0,16 [IC 0,03−0.99]). Los pacientes CIR requirieron un ingreso más prolongado y más días de nutrición parenteral, así como una mayor incidencia de alteraciones hematológicas como neutropenia y trombopenia. El valor de lactato al nacimiento fue mayor en el subgrupo CIR grave (6,12 vs. 2,4 mg/dl, p = 0,02). Conclusiones: El diagnóstico de CIR precoz moderado-grave definido por criterios doppler conlleva un mayor riesgo de morbilidad respiratoria, nutricional y hematológica, independiente del peso y la edad gestacional. Estos pacientes, por tanto, deben ser considerados de mayor riesgo que pretérminos constitucionalmente de bajo peso o pretérminos no CIR.